Gernika filmea - Acha, Enrique; Agirre, Mikel; Garcia, Mariasun; Euskal Irrati Telebista; Baleuko; ITESA producciones; Bizkaiko Foru Aldundia ([S.l.] : Enrique Acha, 1987)
Gernikako bonbardaketaren gaineko dokumentala.
Keywords: Gernika-Lumo -- Historia -- 1937 (Bonbardaketa); Euskadi -- Historia -- 1936-1939 (36ko Gerra); Baliabide digitalak; Dokumentalak